Leukemia inhibitor factor promotes functional recovery and oligodendrocyte survival in rat models of focal ischemia. (16th July 2014) - Rowe, Derrick D.; Collier, Lisa A.; Seifert, Hilary A.; Chapman, Cortney B.; Leonardo, Christopher C.; Willing, Alison E.; Pennypacker, Keith R.
Abstract Human umbilical cord blood (HUCB) cells have shown efficacy in rodent models of focal ischemia and in vitro systems that recapitulate stroke conditions. One potential mechanism of protection is through secretion of soluble factors that protect neurons and oligodendrocytes (OLs) from oxidative stress. To overcome practical issues with cellular therapies, identification of soluble factors released by HUCB and other stem cells may pave the way for treatment modalities that are safer for a larger percentage of stroke patients. Among these soluble factors is leukemia inhibitory factor (LIF), a cytokine that exerts pleiotropic effects on cell survival. Here, data show that LIF effectively reduced infarct volume, reduced white matter injury and improved functional outcomes when administered to rats following permanent middle cerebral artery occlusion. To further explore downstream signaling, primary oligodendrocyte cultures were exposed to oxygen–glucose deprivation to mimic stroke conditions. LIF significantly reduced lactate dehydrogenase release from OLs, reduced superoxide dismutase activity and induced peroxiredoxin 4 (Prdx4) transcript. Additionally, the protective and antioxidant capacity of LIF was negated by both Akt inhibition and co‐incubation with Prdx4‐neutralising antibodies, establishing a role for the Akt signaling pathway and Prdx4‐mediated antioxidation in LIF protection.